2019
DOI: 10.1093/eurheartj/ehz748.1156
|View full text |Cite
|
Sign up to set email alerts
|

P2846Focal impulse and rotor modulation ablation versus pulmonary vein isolation for the treatment of paroxysmal atrial fibrillation (FIRMAP AF study)

Abstract: Background Based on the assumption of trigger elimination, pulmonary vein isolation (PVI) currently presents the gold standard of atrial fibrillation (AF) ablation. Recently, rapidly spinning rotors or focal impulse formation has been raised as a crucial sustaining mechanism of AF. Ablation of these rotors may potentially obviate the need for trigger elimination with PVI. Purpose This study sought to compare the safety and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the study provides no direct evidence that their approach targeted fibrosis, as they targeted low-voltage areas that are known to have poor spatial correlation with fibrotic areas. In regard to rotor-based ablation, Tilz et al (2020) have shown that PVI had similar effectiveness to FIRM-guided ablation in paroxysmal AF patients. However, (i) their study provided no evidence that the same applies to persistent AF patients and (ii) FIRM is known for its limitations in identifying rotors, and therefore the study points to the limitations of the FIRM approach specifically, rather than of the rotor-based approach in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study provides no direct evidence that their approach targeted fibrosis, as they targeted low-voltage areas that are known to have poor spatial correlation with fibrotic areas. In regard to rotor-based ablation, Tilz et al (2020) have shown that PVI had similar effectiveness to FIRM-guided ablation in paroxysmal AF patients. However, (i) their study provided no evidence that the same applies to persistent AF patients and (ii) FIRM is known for its limitations in identifying rotors, and therefore the study points to the limitations of the FIRM approach specifically, rather than of the rotor-based approach in general.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a significant proportion of rotors have been described in the right atrium (an area not normally targeted during AF ablation) (42), making focal impulse and rotor modulation (FIRM) an appealing adjunctive strategy (43). Although the CONFIRM (Conventional Ablation for Atrial Fibrillation With or Without Focal Impulse and Rotor Modulation) study reported a high degree of freedom from AF with FIRM ( 42), other studies have demonstrated that, despite the association with a more organized fibrillatory activation within the LA, it does not correlate with an increase in freedom from AF, even after redo procedures (43)(44)(45)(46). Furthermore, a head-to-head meta-analysis of six studies including 716 patients (88.5% non-PAF) concluded that FIRM did not add any benefit in improving all-atrial arrhythmia recurrence (47).…”
Section: Rotorsmentioning
confidence: 99%